Coexistence of MSI with KRAS mutation is associated with worse prognosis in colorectal cancer. Issue 50 (December 2016) - Hu, Jing; Yan, Wen-Yue; Xie, Li; Cheng, Lei; Yang, Mi; Li, Li; Shi, Jiong; Liu, Bao-Rui; Qian, Xiao-Ping
Abstract : Abstract: Kristen rat sarcoma viral oncogene homolog (KRAS) and microsatellite instability (MSI) are prognostic markers of colorectal cancer (CRC). However, the clinical value is still not fully understood, when giving the consideration to both the molecular makers. Five hundred fifty-one patients with CRC were retrospectively assessed by determining their clinicopathological features. KRAS mutations were detected by polymerase chain reaction. MSI, a defect in the mismatch repair (MMR) system, was detected by immunohistochemistry. The prognostic value of KRAS in combination with MSI was studied. Among 551 CRC patients, mutations in KRAS codon 12 and KRAS codon 13 were detected in 34.5% and 10.5% of patients, respectively. Four hundred one tumors were randomly selected to detect for MMR proteins expression. In this analysis, 30 (7.5%) tumors that had at least 1 MMR protein loss were defined as MMR protein-deficient (MMR-D), and the remaining tumors were classed as MMR protein-intact (MMR-I). According to KRAS mutation and MSI status, CRC was classified into 4 groups: Group 1, KRAS-mutated and MMR-I; Group 2, KRAS-mutated and MMR-D; Group 3, KRAS wild and MMR-I; and Group 4, KRAS wild and MMR-D. We found that patients in Group4 had the best prognosis. In conclusion, combination status of KRAS and MSI status may be used as a prognostic biomarker for CRC patient, if validated by larger studies.